PERSEPSI MASYARAKAT NELAYAN BAGAN TANCAP ( Lift net ) TERHADAP POLA KERJA PONGGAWA DI TANJUNG JUMLAI KELURAHAN SALOLOANG KECAMATAN PENAJAM KABUPATEN PENAJAM PASER UTARA - Dewi Sartika; Said Abdusysyahid; Ristiyana Eryati (Jurnal Pembangunan Perikanan dan Agribisnis, 2018)
The aim of this Research was to understand fisherman community perception who’s used Lift net towards broker (ponggawa) work pattern and haul production. This research was dont in December to April 2017 at Tanjung Jumlai, Saloloang Subdistrict, Penajam District, Penajam Paser Utara Regency. Sampling methods on this research was used census Method because the fisherman community consists of 35 Lift net fisherman. Data analyzed with integrating qualitative approach to know fisherman community percepsion on broker’s patterns. The result showed that broker work patterns towards the fisherman at tanjung Jumlai was a parton – clien. Thus, relation intertwined vertically in which the of broker aid fisherman community in the economic (production and marketing) and sosial aspect. Then average scale of 8 perception indicators was 1.495 which means fisherman community perception towards broker’s work patterns in Tanjung Jumlai, Saloloang Subdistct, Penajam District, Penajam Paser Utara Regency was in moderate category